Research advancements on agricultural non-point source pollution in major lake and reservoir watersheds of China: Status, sources, monitoring, and prospects - Yuansong Tian; Jian Shen; Jimeng Feng; Tiantian Wang; Yuanmei Jiao; Xinze Wang (Ecological Indicators)
Agricultural non-point source pollution (ANPSP) has become a global environmental issue due to its widespread dispersion, difficulty in treatment, and delayed impact. Compared with point source pollution, the monitoring, pollution load accounting, and management of non-point source pollution have proven to be more challenging, particularly at the watershed scale. To comprehensively assess the current status of control and monitoring of ANPSP in watersheds and formulate new monitoring schemes, this paper reviews the specific situation and research status of ANPSP in major lake and reservoir watersheds of China and specifically analyses the sources of ANPSP in four main dimensions, including farmland cultivation sources, livestock and poultry breeding sources, aquaculture sources, and rural domestic sources. On this basis, we also describe the current technical deficiencies for monitoring ANPSP in key watersheds. This review also puts forth a comprehensive three-dimensional monitoring network, termed “sky-air-land-lake,” and elucidates the present status of monitoring and assessment in each dimension. This study has a positive role and theoretical value in further strengthening ANPSP control technology, improving the quality of the rural ecological environment, and enhancing the output value of cultivation and breeding.